2019
DOI: 10.1177/0300060519888112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics combined with early enteral nutrition on endothelin-1 and C-reactive protein levels and prognosis in patients with severe traumatic brain injury

Abstract: Objective To investigate the effects of probiotics combined with early enteral nutrition on levels of endothelin-1 (ET-1), C-reactive protein (CRP), and inflammatory factors, and on the prognosis of patients with severe traumatic brain injury (TBI). Methods We enrolled 76 adults with severe TBI. The patients were divided randomly into two equal groups administered enteral nutrition with and without probiotics, respectively. Demographic and clinical data including age, sex, Glasgow Coma Scale score, Sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…In a study involving 67 patients, the effects of probiotics combined with early enteral nutrition on the levels of endothelin-1 (ET-1), C-reactive protein (CRP), and inflammatory factors in patients with severe traumatic brain injury (TBI) were investigated, suggesting that probiotics combined with early enteral nutrition could reduce serum ET-1, CRP, IL-6, IL-10, and TNF-α levels in patients with severe TBI, thereby increasing the recovery rate of patients. 23 Horn et al believed that 24 patients receiving high-protein formula enteral nutrition (more than 20% of calories) had a 25% higher recovery rate than those receiving normal protein content, suggesting that clinicians should strongly consider using a formula containing at least 20% of protein when possible, rather than the standard formula.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 67 patients, the effects of probiotics combined with early enteral nutrition on the levels of endothelin-1 (ET-1), C-reactive protein (CRP), and inflammatory factors in patients with severe traumatic brain injury (TBI) were investigated, suggesting that probiotics combined with early enteral nutrition could reduce serum ET-1, CRP, IL-6, IL-10, and TNF-α levels in patients with severe TBI, thereby increasing the recovery rate of patients. 23 Horn et al believed that 24 patients receiving high-protein formula enteral nutrition (more than 20% of calories) had a 25% higher recovery rate than those receiving normal protein content, suggesting that clinicians should strongly consider using a formula containing at least 20% of protein when possible, rather than the standard formula.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found in achievement of target energy delivery or inflammatory outcomes between groups, though those receiving EN with probiotics were found to require less insulin and have lower rates of diarrhea. In another study conducted among patients with severe TBI receiving EN, with and without probiotic supplementation, serum inflammatory markers (IL-6, Il-10, TNFalpha, and CRP) were reported to decrease more significantly among patients receiving a probiotic containing Bifidobacterium, Lactobacillus, and Enterococcus faecalis [91].…”
Section: Critical Care Interventions Impacting the Microbiomementioning
confidence: 96%
“…A total of four articles (7,13,14,16) reported the related outcomes of nutritional support on the mortality of patients with TBI. The results of the heterogeneity test (I 2 =53%; P=0.09) indicated the presence of heterogeneity.…”
Section: Case Fatality Ratementioning
confidence: 99%
“…Four articles (7,13,14,16) reported the occurrence of lung infections in patients with TBI after nutritional support intervention. The analysis indicated I 2 =0%, P=0.99, and the comprehensive analysis results of the fixed effects model showed that the lung infection rate of the nutritional support group was lower than that of the standard nutrition group, RR =0.60, 95% CI (0.45-0.81), and the difference was statistically significant (P=0.0006), as shown in Figure 5.…”
Section: Lung Infection Ratementioning
confidence: 99%
See 1 more Smart Citation